2016
DOI: 10.3233/nre-161372
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in morphometric aspects of the peripheral nerves and related diseases

Abstract: BACKGROUND: The elucidation of the relationship between the morphology of the peripheral nerves and the diseases would be valuable in developing new medical treatments on the assumption that characteristics of the peripheral nerves in females are different from those in males.METHODS: We used 13 kinds of the peripheral nerve. The materials were obtained from 10 Japanese female and male cadavers. We performed a morphometric analysis of nerve fibers. We estimated the total number of myelinated axons, and calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…The current study included mainly female participants, which may have possibly limited the generalizability of the findings. Although research on this topic is limited, previous studies in animals 43 and in humans 44 , 45 have found no consistent differences on vagus nerve morphology between males and females. However, effects of tVNS on LC-NE activity may be different for men and women due to differences in morphology of the LC and CRF1 receptors 46 .…”
Section: Discussionmentioning
confidence: 90%
“…The current study included mainly female participants, which may have possibly limited the generalizability of the findings. Although research on this topic is limited, previous studies in animals 43 and in humans 44 , 45 have found no consistent differences on vagus nerve morphology between males and females. However, effects of tVNS on LC-NE activity may be different for men and women due to differences in morphology of the LC and CRF1 receptors 46 .…”
Section: Discussionmentioning
confidence: 90%
“…They suggested that this could be one reason for the overrepresentation of women in vestibular disorders. In a further study, Moriyama et al (2016) studied the vestibular nerves of 10 Japanese men and 10 women. They again found that women exhibited significantly fewer myelinated axons than men (P Ͻ 0.05), although there was no significant difference in the total number of axons, the average transverse area, or the average circularity ratio of myelinated axons.…”
Section: Anatomic Differences In Humans and Animalsmentioning
confidence: 99%
“…These include a smaller peripheral vestibular system, fewer myelinated axons in the vestibular nerve, and fewer neurons in the MVN, in females. The difference in myelinated axons in the vestibular nerve was suggested by Moriyama et al (2007Moriyama et al ( , 2016 to be a possible explanation for the overrepresentation of vestibular disorders among women, although it is not clear how this might be the case. Presumably, fewer myelinated fibers would mean that vestibular information is transmitted more slowly to the vestibular nucleus and cerebellum.…”
Section: Other Differencesmentioning
confidence: 99%
“…Morphometric analysis of Scarpa's ganglion axons has found no difference between women and men in average transverse area, and significantly fewer myelinated axons in women than in men (18,022 compared with 21,006; Moriyama et al, 2007). Other than the X cranial nerve, the vestibular portion of the VIII cranial nerve was the only one of 13 peripheral nerves to show a sex difference in a morphometric comparison (Moriyama et al, 2016). However, the XI cranial nerve, which innervates the sternocleidomastoid, was not included in the morphometric comparison, and on available data can only be evaluated for sex difference using a conduction study (Cleavenger et al, 2019).…”
Section: Possible Causation Affecting the Vestibulo-collic Reflex Arcmentioning
confidence: 96%